Looking in the mirror: rethinking Western terrorism from a critical perspective - Guerra, Nicola (Informa UK Limited, 2026)
This article calls for a critical reassessment of terrorism studies by focusing on the often-overlooked role of Western states and intelligence services in the orchestration and facilitation of terrorist violence. Drawing on newly declassified documents, historical case studies, and the evolving trajectory of Critical Terrorism Studies (CTS), it interrogates the ideological and geopolitical biases embedded within mainstream scholarship. Special attention is given to European Cold War contexts, where Western powers allegedly supported far-right extremist groups and covert operations for strategic ends. The analysis critiques prevailing Global North-centric narratives and underscores the necessity of incorporating both Global South perspectives and self-reflexive inquiry by Global North scholars. Ultimately, the study contends that terrorism is not merely an "external threat," as it is frequently portrayed within a hegemonic narrative by orthodox scholarship, the intelligence community, security agencies, political actors, and media of the Global North. Rather, it functions as a geopolitical instrument-deployed selectively, including by those who claim to oppose it within the Global North. In conclusion, the study urges the field to "look in the mirror" and confront the uncomfortable continuities that endure within contemporary intelligence and foreign policy frameworks.